Implementación de un sistema de rotación de electrodo de disco rotatorio para evaluar condiciones hidrodinámicas de fluidos en régimen de flujo laminar (2021)
This project allows knowing what is the behavior of the rotating disk electrode under hydrodynamic conditions, thus obtaining the results of its behavior. Throughout this work, the development of a functional prototype of a system of rotating disk electrodes was carried out, through speed control and current handling of the order of nano amperes to evaluate mass transfer coefficients by electro- rotating disk through over potential conditions. To achieve this, this project is carried out with a type of descriptive research, with exploratory study, because it aims to develop a functional prototype of a rotating disk electrode system, handling microcontrollers, electrical noise, therefore, it is about designing or replicating a phenomenon whose variables are manipulated under controlled conditions. The prototype understudy is carried out through study and control groups, in accordance with the guidelines of the scientific method; With which results are achieved, which will be reflected through graphics, indicating the development, construction, preparation, and other aspects of each process carried out to achieve the development of the prototype.